2019
DOI: 10.1530/rep-18-0618
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin in endometriosis-associated infertility-pelvic pain: systematic review and meta-analysis

Abstract: The objective is to study the significance of altered interleukin levels in endometriosis-related infertility or pelvic pain. The present systematic review and meta-analysis includes a discussion on the roles of interleukin in the physiopathology of endometriosis-associated infertility and/or pelvic pain. We included all studies in which interleukins in peritoneal fluid, follicular fluid or serum from patients were measured and that correlated the findings with either peritoneal or deep endometriosis-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 62 publications
0
32
0
12
Order By: Relevance
“…The role of nerve growth factor GF is known in the pathogenesis of ovarian and breast cancer and presumably in polycystic ovarian syndrome. The main symptom of endometriosis that affects 60% of women with endometriosis is pain, wherefore NGF plays here a significant role in the development and sustentation of the disease [ 79 , 80 , 81 , 82 , 83 ]…”
Section: Diagnosis Of Endometriosismentioning
confidence: 99%
“…The role of nerve growth factor GF is known in the pathogenesis of ovarian and breast cancer and presumably in polycystic ovarian syndrome. The main symptom of endometriosis that affects 60% of women with endometriosis is pain, wherefore NGF plays here a significant role in the development and sustentation of the disease [ 79 , 80 , 81 , 82 , 83 ]…”
Section: Diagnosis Of Endometriosismentioning
confidence: 99%
“…There is numerous clinical evidence that infections and inflammatory diseases often impair reproductive functions in females [39][40][41][42]. It is well known that immune-stress can lead to reproductive dysfunction, such as anovulation and amenorrhea [43].…”
Section: Effects Of Inflammation On Fertility: Lps-induced Functionalmentioning
confidence: 99%
“…There are many reports suggesting that women with endometriosis have lower success rates of IVF‐ET 11,12 . More importantly, many researchers have reported changes in the functions of immune cells in the peritoneal fluid and cytokine production such as IL‐1, 13,14 IL‐6, 14,15 IL‐8, 14 IL‐33, 13 TNF‐α, 15‐18 IFN‐γ, 16,17 and VEGF 19,20 by immune cells as the cause of infertility. Changes in endometrial lymphocytes and endometrial receptivity have also been reported 21‐23 .…”
Section: Endometriosis and Infertilitymentioning
confidence: 99%